2019
DOI: 10.1101/812859
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synergistic population encoding and precise coordinated variability across interlaminar ensembles in the early visual system

Abstract: Sensory stimuli are represented by the joint activity of large populations of neurons across the mammalian cortex. Information in such responses is limited by trial-to-trial variability. Because that variability is not independent between neurons, it has the potential to improve or degrade the amount of sensory information in the population response. How visual information scales with population size remains an open empirical question. Here, we use Neuropixels to simultaneously record tens to hundreds of singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 91 publications
(108 reference statements)
0
7
0
Order By: Relevance
“…Previous studies have shown that variability shared within a neuronal population can constrain information propagation between processing stages (Averbeck et al 2006; Denman and Reid 2019; Kohn et al 2016; Lin et al 2015). This is because shared variance within a population may not average out (Azeredo da Silveira and Rieke 2021; Moreno-Bote et al 2014), leading to a deterioration of the population’s coding capacity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that variability shared within a neuronal population can constrain information propagation between processing stages (Averbeck et al 2006; Denman and Reid 2019; Kohn et al 2016; Lin et al 2015). This is because shared variance within a population may not average out (Azeredo da Silveira and Rieke 2021; Moreno-Bote et al 2014), leading to a deterioration of the population’s coding capacity.…”
Section: Resultsmentioning
confidence: 99%
“…Given the hierarchical organization of the visual cortex (Siegle, Jia, et al, 2021,Harris et al 2019), the response variance of a sensory neuron can potentially limit the amount of stimulus information available to downstream circuits (Denman and Reid 2019, Figures 4 G , 7). While past studies have shown the effects of pair-wise correlations on information encoded by a neuronal population (Averbeck et al 2006; Kohn et al 2016; Moreno-Bote et al 2014), a more comprehensive population-level perspective is essential to understanding the brain’s correlational structure (Recanatesi et al 2022; Shea-Brown et al 2008; Trousdale et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Neuropixels is a single shaft multi-channel neural probe consisting of 384 recording channels selectively measuring from 960 recording sites with a spacing between the recording sites of ∼20 μm. For the neural data used in this paper to test the GEMsort algorithm, neural data were recorded by Neuropixels Phase 3A prototype probes (Jun et al 2017) in awake mice, following procedures described in detail elsewhere (Denman and Reid 2019). All animal procedures were approved by the Allen Institute for Brain Science Institutional Animal Care and Use Committee (IACUC).…”
Section: Resultsmentioning
confidence: 99%
“…Previous attempts at measuring how information scales with population size have frequently found noise correlations to either be beneficial (Denman & Reid, 2019) or to not affect information scaling (Cotton et al, 2018;Mendels & Shamir, 2018). These studies focused on smaller populations (<200 neurons in Denman & Reid, 2019; <100 neurons in Mendels & Shamir, 2018) in which sublinear scaling might be hard to identify (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These studies focused on smaller populations (<200 neurons in Denman & Reid, 2019; <100 neurons in Mendels & Shamir, 2018) in which sublinear scaling might be hard to identify (Fig. 1), and in part included spike timing information (Denman & Reid, 2019) in addition to the spike counts used here. Recent recordings from ~20,000 neurons in mouse V1 suggest information about visual stimuli does saturate (Stringer, Michaelos, & Pachitariu, 2019; Fig.…”
Section: Discussionmentioning
confidence: 99%